Ad-hoc networking towards seamless communications - Gavrilovska, Liljana; Prasad, Ramjee ([S.l.] : Springer, 2010)
This book reveals the state-of-the-art in wireless ad-hoc networking. It addresses many complex and open problems for researchers in the field of ad hoc networks. It further discusses some of the key research topics that are expected to promote and accelerate the commercial application of these networks (e.g., MAC, routing, QoS, optimization issues, service discovery, traffic models, mobility, handovers, security). It also presents "killer applications".